Virtual visits to patients with Covid-19 hospitalized in the ICU: experience report of a social worker (Research, Society and Development, 2021)
This study aims to report the experience of a resident social worker who was part of the multidisciplinary communication team responsible for making virtual visits to patients in the Covid-19 ICU at a university hospital in the western of Paraná. It is methodologically based on a descriptive study, of the type experience report, which occurred between June 2020 and September 2021. Thus, the study discusses the situations experienced by the multidisciplinary communication team, security procedures, virtual visitation, patients, families, the challenges faced and the Social Work’s perspective under the presented situation. It is concluded that, despite the structural, logistical and sanitary implications, the implementation of the telecalls was a huge success in benefiting everyone involved and serving as a tool for the execution of both the guidelines of the National Humanization Plan (NHP) and the guarantee of user’s rights.